Phytofabrication of Ag/AgCl silver nanoparticles from the extract of Phoenix dactylifera L. Medjool date seeds: synthesis, characterization and antimicrobial properties - Thirubuvanesvari-Duraivelu, Pushpa; Abd Gani, Siti Salwa; Hassan, Masriana; Halmi, Mohd Izuan Effendi; Abutayeh, Reem Fawaz; Al-Najjar, Mohammad A. A.; Abu-Odeh, Ala’ (Royal Society of Chemistry, 2025)
The persistence of biofilm-associated infections in skin and soft tissues poses a significant challenge in clinical settings, necessitating the development of sustainable alternatives to conventional antimicrobial agents, paired with development of eco-friendly and non-toxic nanomaterials. This study reports phytofabrication of Ag/AgCl nanoparticles (Ag/AgCl-NPs) using ultrasonicated 80% ethanolic extract of Phoenix dactylifera L. Medjool date seeds (MdSE) without using any external reagents, leveraging their rich phytochemical content as natural reducing and stabilizing agents. The synthesized nanoparticles were characterized using UV-visible spectroscopy (UV-vis), field emission scanning electron microscopy (FESEM), high-resolution field emission transmission electron microscopy (HR-FETEM), selected area electron diffraction (SAED), X-ray diffraction (XRD), and energy-dispersive X-ray (EDX) confirming their average size of 16.75 ± 7.25 nm, spherical morphology, crystalline structure, face-centered cubic (fcc) phase, silver and chlorine entities, and high colloidal stability. Phytochemical screening via Fourier transform infrared spectroscopy (FTIR) analysis identified polyphenols, flavonoid, and protein as the key contributors to the reduction of Ag+ ions to Ag0 species, leading to the successful formation of MdSE-Ag/AgCl-NPs. The antimicrobial efficacy of the nanoparticles was evaluated against two pathogenic Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) and one Gram-positive bacteria (Staphylococcus aureus). The synthesized nanoparticles exhibited significant antibacterial activity, with substantial inhibition of bacterial biofilm formation, especially in reducing biofilm development by 73.57% for P. aeruginosa and 88.66% for S. aureus at 1*MIC, respectively. The synthesized MdSE-Ag/AgCl-NPs exhibit promising characteristics, supporting the effectiveness of Medjool seeds as a bioreductant in nanoparticle synthesis. Their notable properties suggest potential applications in modern medicine and clinical applications, particularly for biofilm prevention and management.